Personalized Dietary Recommendations Based on Lipid-Related Genetic Variants: A Systematic Review - Pérez-Beltrán, Yolanda E.; Rivera-Iñiguez, Ingrid; Gonzalez-Becerra, Karina; Pérez-Naitoh, Naomi; Tovar, Juscelino; Sáyago-Ayerdi, Sonia G.; Mendivil, Edgar J. (Frontiers in Nutrition, 2022)
Background: Obesity and dyslipidemias are risk factors for the development of cardiovascular diseases, which are the main causes of morbidity and mortality worldwide. The pathogenesis of these diseases involves environmental factors, such as nutrition, but there are other aspects like genetic polymorphisms that confer susceptibility to developing obesity and dyslipidemias. In this sense, nutrigenetics is being used for the study of the influence of genetic variations on the circulating lipid responses promoted by certain nutrients or foods, in order to provide specific dietary strategies considering the genetic factors in personalized nutrition interventions. Objective: To identify through a systematic review, the potential nutrigenetic recommendations that demonstrate a strong interaction between gene- diet and circulating lipid variations. Methods: This systematic review used the PRISMA-Protocol for manuscript research and preparation using PubMed and ScienceDirect databases. Studies published from January 2010 to December 2020 only in English language and human species were included. Outcomes related to gene-diet interactions and plasmatic lipids variation were considered as main results. Results: About 1,110 articles were identified, but only 38 articles were considered to fulfill the inclusion criteria established on the basis of the data reported. The acquired information was organized based on gene-diet interaction with nutrients and components of the diet, as well as dietary recommendation generated by each interaction: gene-diet interaction with dietary fats, carbohydrates or dietary fiber, gene-diet interaction with nutraceutical or dietary supplementation and gene-diet interaction with proteins. Conclusions: Findings included in this systematic review indicated that a certain percentage of dietary macronutrients, the consumption of specific amounts of polyunsaturated or monounsaturated fatty acids, as well as the ingestion of nutraceuticals or dietary supplements can be considered as potential strategies for the development of a wide range of nutrigenetic interventions since they have a direct impact on the blood levels of lipids. In this way, specific recommendations were identified as potential tools in the development of precision diets and highlight the importance of personalized nutrition. These recommendations may serve as a possible strategy to implement as dietary tools for the preventive treatment and control of alterations in lipid metabolism.